DETERMINATION OF LEVEL OF DRIED CAPSICUM POWDER FOR OPTIMISATION OF SPENT BROILER BREEDER HEN CHICKEN KOFTAS - M.V. Sneha Sharada; J. Indumathi; G. V. Bhaskar Reddy; S. Shakila (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was undertaken to evaluate the effect of different levels of dried capsicum powder on the quality characteristics of chicken koftas. The capsicum dried powder was incorporated at three different levels viz. 2, 4 and 6% in the formulation. The products were analyzed for various physicochemical and sensory attributes. The pH, emulsion stability (83.56±0.011) (%), cooking yield (81.12±0.011) (%), crude protein, crude fat and total ash contents of the products showed significant (P<0.05) decreasing trend with increase in levels of incorporation of dried capsicum powder. However, a significant (P<0.05) increase in the water holding capacity (%), moisture (67.10±0.008) and crude fibre (1.56±0.006) contents of the chicken koftas was observed with increasing levels of incorporation. Sensory evaluation revealed that koftas prepared with 4 per cent capsicum dried powder had superior scores (P<0.05) compared to 2 and 6 per cent. Hence, incorporation of dried capsicum powder at 4 per cent level in chicken koftas was considered to be optimum. (Include some values of important findings).